2008
DOI: 10.1094/phyto-98-9-1029
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Cucurbit leaf crumple virus (Family Geminiviridae, Genus Begomovirus) Infection Is an Adaptive Antiviral Response Associated with Changes in Viral Small RNAs

Abstract: A strong recovery response occurs in cantaloupe (Cucumis melo) and watermelon (Citrullus lanatus) infected with the bipartite begomovirus Cucurbit leaf crumple virus (CuLCrV). This response is characterized by initially severe symptoms, which gradually become attenuated (almost symptomless). An inverse relationship was detected between viral DNA levels and recovery, indicating that recovered tissues had reduced viral titers. Recovered tissues also were resistant to reinfection with CuLCrV; i.e., recovered leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 47 publications
2
36
0
1
Order By: Relevance
“…These results are very similar to those reported for ASBVd and CLCV (Hagen et al, 2008;Markarian et al, 2004). Because BPMV siRNAs continued to accumulate even though PTGS was suppressed, SMV HC-Pro must promote synergism by suppressing PTGS at a step downstream of the production of siRNA from viral dsRNAs by Dicer-like enzymes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are very similar to those reported for ASBVd and CLCV (Hagen et al, 2008;Markarian et al, 2004). Because BPMV siRNAs continued to accumulate even though PTGS was suppressed, SMV HC-Pro must promote synergism by suppressing PTGS at a step downstream of the production of siRNA from viral dsRNAs by Dicer-like enzymes.…”
Section: Discussionsupporting
confidence: 87%
“…The opposite phenomenon has been observed with Avocado sunblotch viroid (ASBVd) and Cucurbit leaf crumple virus (CLCV) where accumulation of siRNAs was correlated with levels of viroid or virus genomic DNAs in infected tissues (Hagen et al, 2008;Markarian et al, 2004), but the accumulation of BPMV-derived siRNAs during recovery and mixed infections with SMV has not been investigated.…”
mentioning
confidence: 98%
“…5B). The recovery phenotype in plants infected with begomoviruses is a type of defense response and is associated with reduced levels of viral DNA (55,56). Results of DNA gel blot hybridization analyses indicated that viral DNA levels were similar and relatively high for all three genotypes at 21 dpi, when infected plants showed severe leaf curl symptoms (Fig.…”
Section: Toldev Is Associated With Tolcd In Peru Andmentioning
confidence: 95%
“…Moreover, both silencing routes may be used to knock down host genes with the help of geminivirus vectors (virus-induced gene silencing [VIGS]) (12,13,20,43,45,51). In this context, the analysis of the methylation status of geminivirus episomal or integrated DNA has revealed important insights (4,11,28,60,62,65).…”
mentioning
confidence: 99%
“…(iii) Transgenes which were expressed under the control of geminivirus promoters were silenced, and their cytosines methylated, if the plants were superinfected with the corresponding virus, and in complement, an increased level of C-methylation was observed for the replicated DNA (4,65). (iv) Recovery of plants was accompanied by elevated C-methylation of geminivirus DNA (28,60,62). (v) Geminivirus suppressors of silencing changed the global methylation profile of plants (11).…”
mentioning
confidence: 99%